Pengaruh Pengalaman Auditor, Audit Tenure, Time Budget Pressure, dan Fee Audit Terhadap Kualitas Audit Pada Kantor Akuntan Publik di Bali - Dewi, Ida Ayu Putu Puspita Candra; Marvilianti, Putu Eka Dianita (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to determine the effect of auditor experience, audit tenure, time budget pressure, and audit fees on audit quality.This study uses a quantitative approach with instruments in it measurement and statistical processing. This research was conducted at the Public Accounting Office in Bali. The population in this study were all auditors who worked at the Public Accounting Office in Bali astmany as 95 people. The sampling method used in this study was purposive sampling method, so that a sample of 63 respondents was obtained. The data of this study were collected using a questionnaire which was then processed by the multiple linear regression analysis test with the help of SPSS version 22. The results of the study stated that (1) the auditor's experience hadea positive and significant effect on audit quality, (2) audit tenure had a positive and significant effect on audit quality, (3) time budget pressure had a negative and significant effect on audit quality, (4) audit fees had an effect positif and significant impact on audit quality, and (5) auditor experience, audit tenure, time budget pressure and audit fees simultaneously have a significant effect on audit quality.